COMPARATIVE CHARACTERISTICS OF MORPHOLOGICAL AND FUNCTIONAL CHANGES IN THE RAT SKIN WITH THE INTRODUCTION OF SILVER NANOPARTICLES OF DIFFERENT SIZES - Сирма, Е.И.; Ульянов, В.О.; Думброва, Н.Е.; Молчанюк, Н.И.; Скобеєва, В.М. (World of Medicine and Biology, 2015)
Data about the estimation of size-depended tissue effects of silver nanoparticles (NP) within the framework of one experiment are absent. Also given not enough data about influence on a basal membrane silver NP of different sizes. These null data do not allow estimating the tissue effects of influence NP and those size-depended properties. So, the objective of this work is to study of features of influence of silver NP of different sizes on the rat skin. Methods. Used spherical silver NP 20, 30, 70 nm were synthesized using citrate. The experiment was conducted on 261 Wistar rats. Effect was assessed on 1, 3, 7, 14, 21, 30, 45 days after subcutaneous administration of 0.01 ml solution of silver nanoparticles. For electron microscopic examination of skin fragments were fixed, ultrathin sections were contrasted by the method of Reynolds. Results. As a result of the introduction of silver NP of different sizes edema, separation, fragmentation and partial homogenization of the basement membrane is marked. In this case, the dependence of the NP size of rate of basement membrane recovery was observed. In impact conditions, recovery was observed at day 14 in the group 30 nm silver NP, at day 21 in the group 70 nm, and recovery was not observed until the end of the experiment in the group 20 nm. NP 20 nm decrease the number of young forms of fibroblasts to 60, 1 ± 4,2% (p